Green Technology, Resilience, and Sustainability - Sanfilippo, Antonio; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer.)
Green and sustainable technologies, which are environmentally friendly and low-carbon, are rapidly growing and are positioned to dominate world$1 (Bs future. Unfortunately, as the negative environmental, health and economic impacts of non-sustainable choices become ever more abominable, there is a clear need to accelerate the penetration of green technologies to create a resilient global society. To do this, renewable energy sources including solar, wind, hydro, tidal, geothermal, and storage concepts must be scaled up, green materials processing technologies must be expanded including recycling, industrial symbiosis and industrial ecology. Society$1 (Bs transportation system must be decarbonized. The world$1 (Bs unsustainable systems must be converted to green resilient systems en masse and new green technologies that remediate environmental desecration but be scaled up. We must anticipate challenges and global catastrophic risks and prepare for them to make a resilient society. Free and open source technological development has been proven to be one of the most potent sources of innovation and rapid technology distribution. Thus, open source green technologies are of particular interest as it couples open source rapid innovation with the much-needed acceleration of green technology deployment. Green Technology, Resilience and Sustainability is an open access international, multi-disciplinary journal in green technology engineering and research focused on solutions for sustainability and global resilience. The journal aims to be a leading peer-reviewed platform and an authoritative source of original research and reviews related to Green Technology, Resilience and Sustainability. Green Technology, Resilience and Sustainability covers research in the following areas that focus on solutions to environmental issues: New green technologies that help improve renewable energy supply Solar Photovoltaic Technology Solar Thermal and Passive Solar Applications Wind Energy Technology Geothermal Technology Wave, Tide and Ocean Energy Technologies Hydro Power and Pumped Storage Renewable Hydrogen Production Technology and Fuel Cells Energy Storage Distributed Generation and Smart Grids Hybrid or Dual Use Concepts (e.g. agrivoltaics, floatovoltaics, BIPV etc.) New green materials processing technologies Recycling systems Green materials Green buildings and construction processes Efficient and sustainable industrial processes Green products Industrial symbiosis Industrial ecology Life cycle assessment and analysis Sustainable chemistry New green technologies that help improve transportation Electric vehicles Battery technology Green urban design and walkable cities Public transport Bicycle engineering New green technologies that remediate environmental desecration Water conservation, purification and treatment Rehabilitation of chemical and nuclear contaminated sites and brown fields Reforestation and methods to prevent illegal logging Green sanitation Pollution reduction and elimination Resilient technologies Sustainable utilization of resources such as land, water, and air Biodiversity preservation Free and open communication systems Education systems Agriculture systems and alternative foods Preparation for disasters: natural and manmade Preparations to reduce global catastrophic risks Technologies that reduce existential risk The journal also welcomes papers on other related topics provided that such topics are within the context of the broader multi-disciplinary scope of Green Technology, Resilience and Sustainability. Green Technology, Resilience and Sustainability publishes original articles that are theoretical, innovative simulations and/or experimental research, and highlight the recent advances on various green technologies that support resilience and sustainability. The journal also welcomes Review Articles, Brief Communication, Case Studies and Opinion Articles, the latter published as Viewpoints. .s
Keywords: Engineering; Renewable energy sources; Technology and Engineering; Renewable Energy